Outras formas de olhar: construção de imagens a partir da apreciação de filmes com audiodescrição - Duarte, Fabiane Urquhart (2016)
This research titled “Other ways of looking: image building since the observation of movies with audiodescription”, developed in the area of concentration of Educational Technologies in Network for Innovation and Democratization of Education, line of Educational Technologies in Net at the Professional Master in Educational Technologies in Net of the Federal University of Santa Maria, has the purpose to approach cinema and audiovisual and the school reality to students with visual impairment from appreciation of movies and scenes containing the audiodescription resource. In order to understand and qualify appreciation of films with audiodescription, it was held an investigation about the image-building process based on Gilbert Simondon images cycle. Aiming to explore such issues in empirical field, meetings were held, where the students could explore this construction images by assessing the movies, through tactile-gestural and sound experiences, and discussions and dialogues promoted. In this research is used the methodology of cartography, as this methodology is in line with the field study of subjective perceptions to which it is believed that is research aligns.Regarding the field of Educational Technology on the Net, this research aims to be a source of studies for future interventions in the field of educational inclusion through the suggestion of tactile-gestural workshops with students with visual disabilities and seers students and distribution of materials of audio description in Community Collaborative Data.